2019
DOI: 10.1016/j.pquantelec.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Design and realization of light absorbers using plasmonic nanoparticles

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 117 publications
(135 reference statements)
0
9
0
Order By: Relevance
“… 20 It was found that the number and type of stacking faults determine the shape transformation into triangular and hexagonal nanoplates with mirror and center symmetry, respectively. 19 Due to the pronounced plasmonic effect, silver metal nanoparticles have found applications exploiting their photothermal effects, 21 for optoelectronic circuits, 21 as light absorbers, 22 for harvesting energy from microwaves to visible light, 23 for improving cancer diagnosis, 24 for their antibacterial activity, 25 and for flexible electronics, 26 colorimetric sensing, 27 photoacoustic imaging, 28 plasmon assisted chemistry, 29 etc. In addition to the special optical properties of nanoplate morphology, it was found that stacking faults and twin boundaries at the edges of nanoplate crystals enhance the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“… 20 It was found that the number and type of stacking faults determine the shape transformation into triangular and hexagonal nanoplates with mirror and center symmetry, respectively. 19 Due to the pronounced plasmonic effect, silver metal nanoparticles have found applications exploiting their photothermal effects, 21 for optoelectronic circuits, 21 as light absorbers, 22 for harvesting energy from microwaves to visible light, 23 for improving cancer diagnosis, 24 for their antibacterial activity, 25 and for flexible electronics, 26 colorimetric sensing, 27 photoacoustic imaging, 28 plasmon assisted chemistry, 29 etc. In addition to the special optical properties of nanoplate morphology, it was found that stacking faults and twin boundaries at the edges of nanoplate crystals enhance the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of the diffusivity presented in the samples studied, the design of UV-VIS nanoantenas with minimal energy dissipation can be contemplated in comparison to sensitive nanoantenas with infrared response [ 50 ]. In addition to good light absorption and energy dissipation, plasmonic NPs have been studied for applications related to sensors and nanoswitches by coupling light with the NPs [ 51 ]. The application of optical nanoantenas in binary logic operations has also been explored [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…where, V 1 and V 2 are the volume of the core and the shell, respectively. However, the optical absorption and scattering cross sections are expressed as [19][20][21]   …”
Section: Analysis and Discussionmentioning
confidence: 99%